Factor influencing the level of Islamic retail banking adoption by consumers in Malaysia / Mohamad Izzuddin Ibrahim - Ibrahim, Mohamad Izzuddin (2019)
The issues of accountability, trustworthiness and reliability of the financial service provider has been discussed since the starts of modern trading era. The history of banks acting unethically has cumulatively cost billions to the financial consumers. As the world pragmatically and dynamically changing, Islamic finance industry growing bigger and stronger with year on year market growth exponentially increase by 6.9%. As the consumers now having options to choose either conventional or Islamic financing product suits them most, the issues of governance emerge involving Islamic Financial Service (IFS) provider. The consumers aware and question the accountability, trustworthiness and reliability of the IFS in offering Islamic Retail Banking (IRB) to the market. This study analysed the factors (IRB Attributes, Promotional Effort and Perceived Information Quality) effecting the adoption of IRB products by Malaysians and later thoroughly examined either the IFS, during exercise of such factors, did or did not breaching or endangering and compromising the ethicality of corporate governance principle. The finding of this study suggests that there is significance relationship between IRB Attributes, Promotional Effort and Perceived Information Quality toward adoption of IRB products in Malaysia, with promotional effort being the most influential factor affecting the decision to acquire IRB products. The finding also found that there is less governance concern from the consumers' perspective, as they view the IFS might, in some situation, did not manipulating the IRB attributes, promotional material and quality of information delivered to the consumers in unaccountable manner. Hence, the IFS is acting legitimately ethical.